Conclusions for agricultural commercialization policy - von Braun, Joachim; Kennedy, Eileen T. (International Food Policy Research Institute, 1994)
Agricultural commercialization, economic development, and nutrition are linked with one another. Policies influence the strength and direction of these linkages and welfare outcomes. Ignoring the linkages may be to the disadvantage of the nutritional welfare of the poor; opportunities to improve the well-being of the poor may be lost. In this concluding chapter, we attempt to draw some generalized lessons from the receding chapters.